2018
DOI: 10.21149/8087
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of insecurity regarding organized crime in Tamaulipas, Mexico

Abstract: Although the strategies used attempt to reduce the impact of insecurity on mental health, a transformation of mobility in public space and social relations is observed. Citizens handle insecurity at the individual level, even when it is attributed to structural causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…In the second section, Relative Frequency Worry Index was used to analyse the frequency of worry about crime types; Factor Analysis was used to examine the factors influencing fear and feeling of insecurity in the study area. Associated factors influencing fear and feeling of insecurity among the respondents were measured using 24 variables that were established in the literature (Hilliard & Baloglu, 2008;Pain R. , 2000;Badiora & Afon, 2013;Almanza-Avendano, Romero-Mendoza, Luis, & Hortensia, 2018;Azaola, 2012;Reid, Appleby-Arnold, Brockdorff, Jakovljev, & Zdravkovic, 2020;Ojo & Ojewale, 2018). Factor analysis was used to group the rated twenty-four (24) variables 0 into a few numbers of factors (Popoola, Oladehinde, & Animasaun, 2021;Reid, Appleby-Arnold, Brockdorff, Jakovljev, & Zdravkovic, 2020).…”
Section: Data Source Collection Procedure and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the second section, Relative Frequency Worry Index was used to analyse the frequency of worry about crime types; Factor Analysis was used to examine the factors influencing fear and feeling of insecurity in the study area. Associated factors influencing fear and feeling of insecurity among the respondents were measured using 24 variables that were established in the literature (Hilliard & Baloglu, 2008;Pain R. , 2000;Badiora & Afon, 2013;Almanza-Avendano, Romero-Mendoza, Luis, & Hortensia, 2018;Azaola, 2012;Reid, Appleby-Arnold, Brockdorff, Jakovljev, & Zdravkovic, 2020;Ojo & Ojewale, 2018). Factor analysis was used to group the rated twenty-four (24) variables 0 into a few numbers of factors (Popoola, Oladehinde, & Animasaun, 2021;Reid, Appleby-Arnold, Brockdorff, Jakovljev, & Zdravkovic, 2020).…”
Section: Data Source Collection Procedure and Analysismentioning
confidence: 99%
“…The study discovered that age, length of residency, availability of security, and localities were negatively correlated while gender, house type, level of education, and rate of criminal activities were positively correlated to influence fear and feeling of insecurity. Furthermore, Almanza-Avendano et al (2018) found that government failures, organized crime, corruption, moral causes, economic needs, lack of education, and social causes were the perceived factors of insecurity. These factors were confirmed by Azaola (2012) and Jusidman (2012) who noted that social crisis is attributed to unemployment, lack of job security, and inability to have access to education as well as moral degradation that relates to greed, the pursuit of easy money and lack of values contributed to fear and feeling of insecurity among the respondents.…”
mentioning
confidence: 99%
“…Debido a que las encuestas sobre inseguridad suelen considerar a personas mayores de 18 años, e incluso los pocos estudios sobre el sentimiento de inseguridad han sido realizados con adultos (Almanza, Romero & Gómez, 2018), los objetivos de este estudio son comprender el sentimiento de inseguridad, analizar las condiciones contextuales vinculadas al sentimiento de inseguridad y, explorar las dimensiones personal y pública del sentimiento de inseguridad de estudiantes de secundaria de Mexicali. La dimensión personal abarca el sentido otorgado a la inseguridad, la afectividad y las estrategias empleadas para protegerse, mientras que la dimensión pública abarca la interpretación del origen de la delincuencia, el posicionamiento respecto a las estrategias requeridas para su abordaje y la responsabilidad otorgada a los actores sociales ante el problema.…”
Section: El Contexto De Estudio: Mexicali Baja Californiaunclassified
“…Se realizaron diez grupos focales, cinco con hombres y cinco con mujeres, asumiendo que el sentimiento de inseguridad es diferente entre hombres y mujeres, y que expresar dicho sentimiento sería más fácil en grupos del mismo sexo. Se tomó esta decisión debido a que, aunque la vulnerabilidad de jóvenes en la frontera norte de México se ha incrementado en los últimos años por la inseguridad asociada al crimen organizado (Almanza et al, 2018); hombres y mujeres presentan una vulnerabilidad diferenciada ante la inseguridad en el espacio público. Mientras las mujeres suelen enfrentar situaciones como el acoso sexual, los hombres se enfrentan con mayor frecuencia a delitos como la desaparición forzada y los homicidios (Organización Mundial de la Salud [OMS], 2020).…”
Section: Procedimientounclassified